2019
DOI: 10.1089/cap.2018.0110
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Escitalopram/Citalopram-Related Weight Gain in Children and Adolescents: A Natural Language Processing-Based Electronic Medical Record Study

Abstract: Time to first weight gain concern during treatment with escitalopram/citalopram is associated with race (p = 0.01, log-rank test for trend, A), but not gender (p = 0.58, B). (A) White patients are shown in gray and black or other races are shown in black. (B) Males are shown in gray and females are shown in black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Two important treatment-related side effects of escitalopram are weight gain and activation. First, CYP2C19 activity may influence weight gain in this vulnerable population, a finding which may help explain variability in weight gain that has been prospectively observed in escitalopram-treated youth (Czaja et al, 2013; Calarge et al, 2017; Ramsey et al, 2018a). Second, activation, a constellation of side effects that often cause treatment discontinuation and decrease the likelihood of medication response (Bussing et al, 2013; Luft et al, 2018), was associated with CYP2C19 phenotype; more activation symptoms were reported in patients that metabolize es/citalopram more slowly, even after controlling for concomitant psychotropics.…”
Section: Discussionmentioning
confidence: 99%
“…Two important treatment-related side effects of escitalopram are weight gain and activation. First, CYP2C19 activity may influence weight gain in this vulnerable population, a finding which may help explain variability in weight gain that has been prospectively observed in escitalopram-treated youth (Czaja et al, 2013; Calarge et al, 2017; Ramsey et al, 2018a). Second, activation, a constellation of side effects that often cause treatment discontinuation and decrease the likelihood of medication response (Bussing et al, 2013; Luft et al, 2018), was associated with CYP2C19 phenotype; more activation symptoms were reported in patients that metabolize es/citalopram more slowly, even after controlling for concomitant psychotropics.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of NLP technology is to enable people to use natural language to interact with computer systems to achieve information and to ensure the efficient processing of information in the process of humancomputer interaction. The application of NLP technology is mainly focused on the automatic differentiation of phrases, corpus construction, and grammar research, which makes it widely used in data mining, information retrieval, and machine translation [5,6]. With the steady advancement of Chinese legal society, the open system of the judicial field has gradually improved.…”
Section: Introductionmentioning
confidence: 99%
“…Nonrepresentative samples in brain imaging studies, for example, introduce significant bias that can influence our basic understanding of brain structure and function (LeWinn, Sheridan, Keyes, Hamilton, & McLaughlin, 2017). Similarly, in treatment studies, the combination of both under‐representation in study samples (Pickard, Reyes, & Reaven, 2019), and differential patterns of outcomes that vary by racial and ethnic status (Ramsey et al, 2019) raise the possibility (or likelihood) that interpretation of the broader literature without attention to these important factors may be biased. The general lack of attention to racial and ethnic factors in child and mental health research is not unique – a broad survey of more than 26,000 articles in the psychological literature more broadly over the past 50 years found substantial racial inequities in the publication patterns across a number of journals (Roberts, Bareket‐Shavit, Dollins, Goldie, & Mortenson, 2020).…”
Section: Reporting Of Race and Ethnicity And Implicationsmentioning
confidence: 99%